Study of adipose tissue of Kemerovo piglets: Detection of beige adipocytes - V. A. Pchelkina; I. M. Chernukha; I. A. Korotkiy; N. A. Ilyin (Теория и практика переработки мяса, 2022)
Animals have two types of adipose tissue differing in structure and function: white (WAT) and brown (BAT). Beige adipose tissue (BeAT) is a result of WAT browning, when beige adipocytes appear between white adipocytes in response to exposure to cold, diet or physical activity. BeAT shares morphological and biochemical characteristics with BAT, is thermogenic and dissipates energy in the form of heat, unlike WAT, which is responsible for energy storage. Pigs do not have classic BAT, and modern breeds are sensitive to cold. There is literature information that BeAT has been found in cold-resistant pigs. The aim of the work was to study adipose tissue of piglets of the Kemerovo cold-resistant breed under growing conditions in the cold season and to identify the localization of BeAT. Histological studies have shown two types of adipocytes in subcutaneous fat samples (lateral, backfat and axillary): white, with one large fat droplet, and beige, multilocular. Larger cells were detected in backfat fat (69.36±12.98 µm) compared with lateral (53.25±9.27 µm) and axillary fat (45.94±8.29 µm). Only WAT with a diameter of 35.69±6.96 µm was present in the internal perirenal fat. Raman spectroscopy was used to evaluate the overall fatty acid profile of the tested samples. The main peaks were noted in all samples: 970 cm-1 (=C-H out-of-plane bend), 1266/1272 cm-1 (=C-H symmetrical rock) and 1655 cm-1 (C=C stretching) responsible for unsaturated bonds, and signals at 1297/1301 cm-1 (CH2 twisting), 1430/1460 cm-1 (CH2 symmetrical deformation (scissoring)) and 1735/1746 cm-1 (C=O stretching) corresponding to saturated bonds or ester groups. Internal perirenal fat contained the largest number of saturated fatty acid bonds, subcutaneous axillary fat — the smallest. The average intensity of the peaks was 0.4801010 and 0.639995, respectively. According to the results of gas chromatography, the largest amount of polyunsaturated fatty acids was noted in the subcutaneous fat samples: 20.199 in backfat fat, 21.749 in lateral and 20.436 in axillary fat compared to 18.636 in internal fat. Activation of beige cells in Kemerovo pigs under cold exposure, according to the authors, plays a crucial role in the heat balance, allowing them to tolerate cold without severe shivering. The study of the BeAT formation is of great practical importance for changing energy metabolism and increasing thermogenesis in newborn piglets by genome editing, as well as for improving the quality of pig’s fat.